Merariq Tradition of Sasak Tribe in Social Construction and National Law - Erwinsya, Erwinsya; Handoyo, Eko; Arsal, Thriwaty (Universitas Negeri Semarang, 2020)
Generally, Sasak society still maintains a culture of eloping or kidnapping girls to be wives. The aims of this study were to analyze the existence of merariq marriage tradition as a social construction in Sasak Tribe and how merariq marriage tradition in Sasak tribal is reviewed on the implementation of Law No. 1 of 1974. To achieve the goal, this research uses qualitative methods with descriptive. To collect data, this tehniques are observation, document studies and interviews objectively describing the phenomenon. The 20 informants in this study are; eloping actors, indigenous leaders and environmental chiefs who are divided into 10 informants each in 2 locations. The findings showed that one of the normative teachings contained in the practice of merariq is a sense of pride in the identity of the individual and the identity of the female families is characterized by the desire that the girl married by a man which used the it escape process. The pride has a social contribution to the existence of the family in the middle of the local community. On the other hand, merariq tradition is contrary to Law No. 1 of 1974 on marriage.